The role of climate change in global economic governance - Condon, Bradly J.; Sinha, Tapen (Oxford : Oxford University Press, 2013)
Climate change represents an unprecedented challenge, the effects of which require an urgent and effective international response. This book analyses its effect on both developing and developed countries from an economic, financial, and legal perspective, assessing its interaction with international economic law.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 2, 2013).
Keywords: Climatic changes -- Law and legislation; Climatic changes -- Economic aspects; Environmental law, International